The experiences of teaching practice at the University of Limpopo: Possibilities for curriculum improvement - Modipane, Mpho; Kibirige, Israel (South African Journal of Higher Education, 2016)
The purpose of this paper was to establish experiences of pre-service teachers from the University of Limpopo placed in different schools during Teaching Practice (TP) and how these experiences could be used for curriculum improvement. A qualitative and interpretivistic approach was used to highlight multiple realities and interpretations. Data was collected from thirty six participants: 3 focus group interviews of twelve students each representing 3 streams offered in the School of Education. Content thematic analysis was used to analyse data. Results show that curriculum knowledge and interpretation, workloads, overcrowding, teacher attitudes, lack of resources, mentoring, discipline and coping mechanisms were the key issues from TP experiences. The study concludes that some of these experiences of pre-service teachers could be used to improve teacher education curriculum at the University of Limpopo. The study acknowledges that there are challenges that need further study. Key words: Teaching Practice, Institutional Learning, experiences, terrain, curriculum improvement, programme improvement teacher education